2022
DOI: 10.7554/elife.63405
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sensory modality and control dynamics on human path integration

Abstract: Path integration is a sensorimotor computation that can be used to infer latent dynamical states by integrating self-motion cues. We studied the influence of sensory observation (visual/vestibular) and latent control dynamics (velocity/acceleration) on human path integration using a novel motion-cueing algorithm. Sensory modality and control dynamics were both varied randomly across trials, as participants controlled a joystick to steer to a memorized target location in virtual reality. Visual and vestibular s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…In principle, it is possible to use the learned world model to plan joystick movements ahead of time without any sensory feedback. Although we know from manipulation experiments that monkeys relied on sensory feedback (optic flow), the contribution of autonomous strategies to navigation is likely non-negligible 35 , 66 , 67 . Planning-based computations, which require reasoning about the consequences of action sequences via mental simulation, are thought to be performed in the prefrontal cortex (PFC) 68 , 69 .…”
Section: Discussionmentioning
confidence: 99%
“…In principle, it is possible to use the learned world model to plan joystick movements ahead of time without any sensory feedback. Although we know from manipulation experiments that monkeys relied on sensory feedback (optic flow), the contribution of autonomous strategies to navigation is likely non-negligible 35 , 66 , 67 . Planning-based computations, which require reasoning about the consequences of action sequences via mental simulation, are thought to be performed in the prefrontal cortex (PFC) 68 , 69 .…”
Section: Discussionmentioning
confidence: 99%
“…Our study is one among the few recent studies that tested self-motion perception under a direct coupling between the actions of the participants and the sensory feedback (25)(26)(27). These recent experiments imposed fewer artificial constraints than the traditional open-loop psychophysical paradigms on self-motion perception (e.g., [37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study by Stavropoulos et al (27), human participants controlled their self-displacement on a motion platform to navigate to a target with and without the presence of concurrent optic flow. They found that steering behavior in darkness was biased (i.e., participants undershot the target location), and therefore concluded that participants could not accurately estimate their self-motion and update their internal model based on the vestibular cues alone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations